New matK initiators for life barcode in species of the genus Dasylirion - Orozco-Sifuentes, Martha Monzerrath; Mendoza-Rodríguez, Dulce Victoria; Hernández-Godinez, Fernando; Martínez, Octavio; Villarreal-Quintanilla, José Ángel; Reyes-Valdés, M. Humberto (Revista Mexicana de Ciencias Agrícolas, 2019)
Dasylirion species are among the most important in the Chihuahuan Desert in ecological and economic terms. Its main use is the elaboration of a traditional alcoholic beverage called sotol. The genus comprises 22 species, not all suitable for this purpose and their identification is difficult. Molecular tools such as the barcode of life facilitate their identification and generate genetic information. There are universal primers for the matK gene, whose sequence is appropriate for life’s barcode, which do not work for some species of this genus. The difference of a single nucleotide can cause problems in amplification. The objective of this work was to design and test new initiating sequences of the matK gene, which allow amplification in plants of the genus Dasylirion. The Primer3 Plus, FastPCR and the complete sequence of the matK gene of D. wheeleri were used for the design. The new oligonucleotides were tested with the species D. texanum, D. leiophyllum, D. occidentalis and D. palaciosii, with clean amplification of the matK gene (approximately 1 000 bp fragment) in each of them. These results contrasted with those obtained from the universal primers matK 390F and matK 1 326R, which generated secondary bands or failed amplification. Since the new initiators successfully amplified the matK gene in the studied species of Dasylirion, they are considered of value as tools for obtaining the barcode of life in sotol. Research conducted during the years 2016 to 2018.